Does the stock market affect firm investment in China? A price informativeness perspective - Wang, Yaping; Wu, Liansheng; Yang, Yunhong (Journal of Banking & Finance, 2009)
This paper investigates the empirical relationship between firm-level investment and the stock market in China from a price informativeness perspective. We find that firm investment does not significantly respond to the stock market valuation, because stock prices contain very little extra information about the future operating performance of firms. This finding is further supported by the relative investment response test and the relative price information content test based on the informativeness proxy of price non-synchronicity combined with firm information transparency.